M6A Regulatory Genes Play an Important Role in the Prognosis, Progression and Immune Microenvironment of Pancreatic Adenocarcinoma. (2nd February 2021) - Xu, Fangshi; Zhang, Zhengliang; Yuan, Miao; Zhao, Yidi; Zhou, Yang; Pei, Honghong; Bai, Ling
Abstract: The specific roles of N6-methyladenosine (m6A) regulatory genes in pancreatic adenocarcinoma (PAAD) have not been fully elucidated. In present study, a novel risk signature was constructed by five m6A-related genes (including METTL3, METTL14, KIAA1429, ALKBH5 and YTHDF1) and was identified as an independent prognostic factor (HR = 13.192) via TCGA (185 samples) databases. The immune abundances of 22 leukocyte subtypes in each PAAD sample were exhibited via the CIBERSORT algorithm. High risk group promoted infiltration levels of Macrophages M0 and M2 cells and decreased that of B cells naive, T cells CD8 and T regulatory cells.